An electrical plasma dissection tool for surgical treatment of chronic ulcers: Results of a prospective randomised trial. Issue 5 (30th March 2018) - Marangi, Giovanni F; Pallara, Tiziano; Lamberti, Daniela; Perrella, Eleonora; Serra, Raffaele; Stilo, Francesco; De Caridi, Giovanni; Onetti Muda, Andrea; Persichetti, Paolo
Abstract : Cutaneous ulceration is a difficult medical problem and a major source of morbidity for patients. In the surgical treatment of ulcers, debridement is the first step, and it can be carried out using several surgical tools. Recently, new surgical devices have emerged using plasma‐mediated electrical discharges with a lower peak temperature. A prospective single‐blind trial was conducted on chronic ulcers not responsive to common non‐surgical management. Patients were randomly separated into 2 groups: Group A received surgical debridement with conventional electrocautery, and Group B received surgical debridement using the plasma‐mediated device. Histological samples were collected intraoperatively to evaluate the thermal damage during the surgical procedure and 2 weeks after surgery to evaluate the inflammatory response and collagen deposition. The width of coagulation necrosis at the incision margins in Group B was significantly shorter compared with Group A ( P = .001). The inflammatory cell infiltration showed a cellular distribution percentage that was quite equal between the 2 groups. The granulation tissue showed an abundant deposition of dense and mature collagen in Group B, compared with Group A, where the mature collagen appeared in small quantities ( P < .001). Microbial culture showed a lower incidence of postoperative infections in Group B compared with the control group ( P < .05). The study demonstrated, based on the results, that the new technology with the use of a lower temperature electrosurgical device represents an effective therapeutic weapon for the surgical treatment of skin ulcers, both vascular and extravascular types.